2011
DOI: 10.1088/0964-1726/20/7/075022
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of a Duffing oscillator for broadband piezoelectric energy harvesting

Abstract: Vibration energy harvesters are usually resonant mechanical systems working at resonance. The subsequent mechanical amplification results in output powers multiplied by the mechanical quality factor when compared to non-resonant systems. The main drawback is the difficulty of matching a given vibration frequency range to the energy harvester's resonance frequency. Among several techniques, the use of nonlinear mechanical resonators was proposed in several studies for enlarging energy harvester power bandwidth.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 38 publications
3
83
1
Order By: Relevance
“…In general, different from previous studies for PE or EM energy harvester [32,35,37], nonlinearities generated by additional magnet interactions could be beneficial for hybrid PE and EM As shown in Figure 6, output performances based on analytical expressions of nonlinear hybrid piezoelectric and electromagnetic energy harvester are consistent with theoretical results through Energies 2018, 11, 498 13 of 23 solving 45 linearly coupled equations, the difference between modeling values obtained by two theoretical models is rather small. As a consequence, it demonstrates that it is feasible to predict output characteristics of nonlinear hybrid PE and EM energy harvester under colored excitation using the presented theoretical model again.…”
Section: Effects Of Load Resistances and The Excitation's Spectral Decontrasting
confidence: 46%
See 3 more Smart Citations
“…In general, different from previous studies for PE or EM energy harvester [32,35,37], nonlinearities generated by additional magnet interactions could be beneficial for hybrid PE and EM As shown in Figure 6, output performances based on analytical expressions of nonlinear hybrid piezoelectric and electromagnetic energy harvester are consistent with theoretical results through Energies 2018, 11, 498 13 of 23 solving 45 linearly coupled equations, the difference between modeling values obtained by two theoretical models is rather small. As a consequence, it demonstrates that it is feasible to predict output characteristics of nonlinear hybrid PE and EM energy harvester under colored excitation using the presented theoretical model again.…”
Section: Effects Of Load Resistances and The Excitation's Spectral Decontrasting
confidence: 46%
“…Daqaq et al [32] demonstrated that the expected value of the output power will decrease with the stiffness-type nonlinearity. After verification through numerical and experimental methods, Sebald et al [35,37] reached a similar conclusion for a Duffing-type PE oscillator under colored excitation. Nevertheless, the effects of introducing nonlinear stiffness into a randomly excited hybrid PE and EM energy harvester on output characteristics could be quite different.…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…This is so either because design constraints make linear response unattainable, or because nonlinearities are believed useful in tailoring the device behaviour to the vibration of the environment. Examples of strongly nonlinear devices are found among harvesters of all the three main transducer types, i.e., electromagnetic [2][3][4], piezoelectric [5][6][7][8][9] and electrostatic [10][11][12][13][14] generators.…”
Section: Introductionmentioning
confidence: 99%